Reaction Microscope experiments with shaped laser pulses. Issue 12 (January 2020) - Farfán, D Martínez; Fross, P; Kerbstadt, S; Mi, Y; Camus, N; Sun, X; Wollenhaupt, M; Pfeifer, T; Moshammer, R
Synopsis: Using a 4f pulse shaper in combination with a Reaction Microscope we performed 800 nm pump-probe experiments with orthogonally polarized pulses on H₂.